The Impact of Scarcity of Health Supplement Products' Impacts on Impulsive Purchasing during the COVID-19 Pandemic in Indonesia - Elisa, Hanifah Putri; Fakhri, Mahendra; Pradana, Mahir (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
The peak of the COVID-19 outbreak in Indonesia occurred in 2020, causing a scarcity of health supplement products that significantly impact consumers' impulsive purchases and public safety. During this challenging period, it is crucial to understand the impact of scarcity on customers' impulsive purchases. However, little research has been done in Indonesia on the impact of health supplement scarcity on impulsive purchases. Based on scarcity and SOR theories, this research investigates the impact of scarcity of health supplement products on customers' impulsive purchases during pandemics in Indonesia. In short, the study identified the mechanisms of mediation (fear of missing out) and moderation (social media fake news) in the relationship between scarcity and impulsive purchasing. Ultimately, 170 valid data points were acquired using online surveys, and SmartPLS was used for data analysis. As the results showed that fear of missing out dominates the impact of the scarcity of impulsive purchases. The study provides more information about consumers' impulsive purchases given the scarcity of health supplement products in times of pandemics. Businesses and the Indonesian government can take steps to reduce the impact, hich might help keep the country safe throughout the pandemic.